Mend! : a refashioning manual and manifesto - Sekules, Kate (Penguin Books, 2020)
"A guide to the art, history, and politics of visible mending--at once a practical instruction guide for techniques, a statement on the beauty of repairing and reimagining clothes, and a manifesto against fast fashion. Part manifesto, part how-to, this book persuasively calls for a new way of thinking and handling clothes, flying in the face of the supposedly life-changing magic of throwing them away. Kate Sekules's message is simple: If your sweater gets a hole in it, don't discard it--mend it! Changing the way we dress is easier and cheaper than we think, and with enthusiasm and wit, Sekules shows you how to fix your garments and make your wardrobe more interesting with visible mending techniques, and help save the planet (and your soul) in the process. The environmental and human impacts of our clothing consumer habits cannot be overstated. When we continually buy and discard clothes, we are contributing to pollution, exploitation, and the waste of natural resources. Instead, we should be buying less and better, swapping, embracing vintage, and of course, mending. Sharp and incredibly timely, Mend! is a push for a slow fashion revolution in which we stop to think critically about what we buy, where it comes from, who makes it, and what it is doing to the environment, and is simultaneously a fun, crafty manual that will inspire readers to roll up their (freshly mended) sleeves and get creative, share their designs, and form radical creative communities to change closets, lives, and the world"--